2018
DOI: 10.12688/wellcomeopenres.14706.1
|View full text |Cite
|
Sign up to set email alerts
|

Modifying Intestinal Integrity and MicroBiome in Severe Malnutrition with Legume-Based Feeds (MIMBLE 2.0): protocol for a phase II refined feed and intervention trial

Abstract: Background: Changes in intestinal mucosal integrity and gut microbial balance occur in severe acute malnutrition (SAM), resulting in treatment failure and adverse clinical outcomes (gram-negative sepsis, diarrhoea and high case-fatality). Transient lactose intolerance, due to loss of intestinal brush border lactase, also complicates SAM, thus milk based feeds may not be optimal for nutritional rehabilitation. Since the gut epithelial barrier can be supported by short chain fatty acids, derived from microbiota … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
13
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1
1

Relationship

4
3

Authors

Journals

citations
Cited by 8 publications
(13 citation statements)
references
References 22 publications
0
13
0
Order By: Relevance
“…58 In our proof-of-concept study, we demonstrated no adverse effects of the feed, which has resulted in a phase II trial using a food industry standard feed developed by a commercial partner. 59 The children randomized to the CpF gain a similar amount of weight, had increased mid-upper arm circumference, and had no difference in diarrheal episodes compare to ConFs. In fact, our data indicated legume-enriched feeds reduced the impact of antibiotics on further lowering the diversity of the microbiota early in the course of admission/nutritional rehabilitation.…”
Section: Discussionmentioning
confidence: 89%
“…58 In our proof-of-concept study, we demonstrated no adverse effects of the feed, which has resulted in a phase II trial using a food industry standard feed developed by a commercial partner. 59 The children randomized to the CpF gain a similar amount of weight, had increased mid-upper arm circumference, and had no difference in diarrheal episodes compare to ConFs. In fact, our data indicated legume-enriched feeds reduced the impact of antibiotics on further lowering the diversity of the microbiota early in the course of admission/nutritional rehabilitation.…”
Section: Discussionmentioning
confidence: 89%
“…The safety and efficacy of the resultant product will be assessed in a phase II randomised controlled trial 25 . Briefly, the MIMBLE II trial is an open-label controlled trial in 160 Ugandan children with SAM, defined by mid-upper arm circumference < 11.5cm and/or presence of kwashiorkor.…”
Section: Future Investigationmentioning
confidence: 99%
“…We describe the development process of a lactose-free, fermentable carbohydrate-containing alternative to traditional F75 and F100 formulae for the treatment of SAM, for use in a phase II controlled clinical trial in Uganda: Modifying Intestinal MicroBiome using Legume-based feeds (MIMBLE II) 25 .…”
Section: Introductionmentioning
confidence: 99%
“…However, this has not been translated to the formulae used in children with SAM in low- and middle-income countries where case fatality remains a major problem 24 . Our research group have developed and tested in a Phase II trials legume-based formulae for children with SM aimed at optimising gut function and ‘feeding the microbiome’, which has provided early indications of improved gut health and better clinical outcomes 25 , 26 .…”
Section: Introductionmentioning
confidence: 99%
“…We describe the development process of a lactose-free, fermentable carbohydrate-containing (chick-pea) alternative to traditional F75 and F100 formulae for the treatment of SAM, for use in a phase II controlled clinical trial in Uganda: Modifying Intestinal MicroBiome using Legume-based feeds (MIMBLE II) 25 .…”
Section: Introductionmentioning
confidence: 99%